Helicobacter pylori y cáncer gástrico. - Cuenca Buele, Sylvana Alexandra; Lozano, Iria; Jara Guerrero, Edmo; Ganán Romero, Manuel (Universidad Técnica de Machala, 2021)
Helicobacter pylori (H. pylori) is a microorganism associated with gastric cancer and premalignant lesions of the stomach. Research on this subject is carried out a large scale worldwide, which makes it necessary to constant-ly update this subject through bibliographic reviews of scientific articles. This is a descriptive, retrospective study, based on obtaining systematic do-cumentary information from research carried out in different parts of the world. Databases such as: PubMed, ScIELO, Science Direct and Scholar Goo-gle were used and articles from the last 5 years were selected. Thirty-five articles were included in the results. H. pylori has a higher incidence in coun-tries where gastric cancer is more frequent. Premalignant lesions appear after colonization of the microorganism years before the cancer occurs; the greater the morphological alteration found, the greater the probability of developing cancer. H. pylori infection is enhanced in the presence of genetic, environmental, dietary and socioeconomic factors of the population. Eradi-cation of this bacterium decreases the incidence of gastric cancer. It can therefore conclude that H. pylori is involved in the genesis of gastric cancer 23Helicobacter pylori y cáncer gástricoREVISTA CIENTÍFICAand its premalignant lesions. In countries where H. pylori has a higher inci-dence, the incidence of gastric cancer is also high. Definitive eradication of H. pylori from the gastric mucosa decreases both the incidence and mortality from gastric cancer.
Helicobacter pylori (H. pylori) es un microorganismo que se relaciona con cáncer gástrico y lesiones premalignas del estómago. Las investigaciones al respecto se producen a gran escala a nivel mundial, por lo que se hace necesaria la actualización constante de esta temática a través de revisiones bibliográficas de artículos científicos. Este es un estudio descriptivo, re-prospectivo, basado en la obtención de información documental sistemática de investigaciones realizadas en diferentes partes del mundo. Se recurrió a bases de datos como: PubMed, ScIELO, Science Direct y Google Académico, se seleccionaron artículos de los últimos 5 años. En los resultados se incluyeron 35 artículos. H. pylori tiene mayor incidencia en países donde es más frecuente el cáncer gástrico. Las lesiones premalignas aparecen tras la colonización del microorganismo años antes de que se produzca el cáncer, mine-tras mayor es la alteración morfológica encontrada, la probabilidad de pre-sentar cáncer es mayor. La infección por H. pylori se potencia en presencia de factores genéticos, medio ambientales, alimentarios y nivel socioeconómico de la población. La erradicación de esta bacteria disminuye la incidencia de cáncer gástrico. Podemos concluir entonces que H. pylori está involucrado en la génesis del cáncer gástrico y sus lesiones premalignas. En países donde H. pylori tiene mayor incidencia también es alta la incidencia por cáncer gástrico. La erradicación definitiva de H. pylori de la mucosa gástrica disminuye tanto la incidencia como la mortalidad por cáncer gástrico.
Keywords: HELICOBACTER PYLORI; PATOLOGÍAS; PREMALIGNAS; CÁNCER GÁSTRICO